Surface-enhanced raman scattering from a layer of gold nanoparticles - Binh, Nguyen The; Dinh, Nguyen Thanh; Dong, Nguyen Quang; Thu, Vu Thi Khanh (VNU Journal of Science: Mathematics - Physics, 2010)
Abstract